PENYULUHAN HUKUM JUAL BELI MENURUT HUKUM BISNIS DAN SYARIAH BAGI MASYARAKAT MUSLIM DI KELURAHAN CEMPAKA BARU KEMAYORAN JAKARTA PUSAT - Endang Purwaningsih; Irfan Islami; Haban Rofiq (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2018)
With the condition of a plural society and the majority of Moslems, the Moslems also needs to be equipped with knowledge about trading law either based on business law and sharia, which may be applied in transactions every day in trading activities. Need awareness and legal provisions in the economic world being more global, so that Moslems understand more about a law and do not become victims of adverse transactions. It is caused the law awareness and law knowledge of the Moslems in Cempaka Baru is still quite low. So, it is necessary to conduct empowerment through law counseling in order to improve their awareness of law either in business transactions or positive law and sharia and the right empowerment model to apply to the Moslems in Cempaka Baru. This counseling and training activities were done with lecturing and training by giving pre-test and post-test, which were held cooperating with village officials of Cempaka Baru, Kemayoran, Central Jakarta. Empowerment effort which was conducted to the Muslims related to the efforts of improving their awareness of law either in business transactions or positive law and sharia is the active participation of citizens and officials and helping hands by campus parties and related institutions. The right empowerment model to apply to the Moslems in Cempaka Baru is through socialization, education, and training and accompanied by the officials and campus, as well as the importance of active participation of Moslems themselves. DOI: https://doi.org/10.26905/abdimas.v2i2.1813